Food, pots and socio-economic transformation: The beginning and intensification of pottery production in North China. (December 2017) - Shelach-Lavi, Gideon; Tu, Dongdong
Abstract: Ceramic is one of the most transformative and enduring technologies in human history. This paper addresses the development of pottery production in North China since its appearance during the late Pleistocene, and through its development and use first by hunter-gatherer societies and then by the early sedentary village communities. We analyze the economic and social context for the beginning of pottery production in North China and argue that pottery was a transformative agent in the dramatic dietary and social changes that occurred prior to and during the transition to agriculture. At the same time, pottery technology and pottery production were also transformed by this trajectory, especially during the relatively rapid transition to large-scale sedentary villages that took place in North China. A model is developed to chart the feedback processes that embody this trajectory.